STRUKTUR DAN PERAN ANEKA LEMBAGA DALAM RANTAI PASOK TERNAK DAN DAGING SAPI POTONG DI PROVINSI NUSA TENGGARA TIMUR (Structure and role of of various institutions in supply chain of cattle and beef comodities in East Nusa Tenggara Province) - Arnoldus Keban; Sirilus S. Niron; Ulrikus Romsen Lole (JURNAL NUKLEUS PETERNAKAN, 2020)
The structure and role of each specific institution in the supply chain management of local cattle marketing need to be known in detail and comprehensively. The objectives were: 1) to describe the various institutional roles in the supply chain management of livestock and beef in Kupang District and Kupang City, NTT; and 2) to formulate efforts to improve the institutional performance of the livestock and beef supply chain in Kupang District, NTT. Surveys of institutions related to supply chain management of beef cattle in a comprehensive manner, covering all stakeholders (farmers, livestock traders, butchers, meat traders, animal markets, slaughterhouses, animal quarantine, sea freight expeditions, etc.). Data were analyzed descriptively- qualitatively and quantitatively, analysis of costs , benefits and margin of each marketing actor. As conclusions were: 1) The role of institutions in the supply chain management of cattle / beef in Kupang Regency is slowly starting to form a solid network according to the roles of the parties. However, they still have problems in terms of smooth communication and interaction in transactions at each point of the supply chain, especially the point between farmers and village traders regarding price determination; and 2) the institutional performance of cattle/ beef supply chain as a whole to ensure the interests of all stakeholders not optimal yet, in particular related to improve the group transaction methods, benchmark prices, controlling the sale of young females, preventing the slaughter of productive females, strict quarantine, and the availability of large capacity livestock vessels.